Characterization and Outcome of Patients Presented with Unilateral Nasal Disease to ENT unit at Hillah, Iraq (Medico Legal Update, 2020)
Background: A common finding during daily otolaryngological practice is a patient with unilateral nasalsymptoms, nasal polyp or mass. The causes behind most cases of unilateral nasal disorder are inflammatoryin nature and responds well to medical intervention and rarely there is need for surgical management. Thepossibility of neoplastic nature is high when there is unilateral nasal complaint or pathology as neoplasticconditions during their early stages may mimic inflammatory pathologies.Aim of the Study: The aim of the current study was to highlight the causes of unilateral nasal disease, theirmost frequent mode of presentation, management strategies and outcome in a sample of Iraqi patients.Patients and Method: The current prospective study included 96 patients, 42 males and 54 females, withsigns and symptoms suggestive of unilateral nasal disease. The study was carried out at Hillah GeneralTeaching Hospital, Babel province, mid-Euphrates region of Iraq and the work with this study has extendedfrom January 2014 to August 2019. All enrolled patients were subjected to routine ENT examination andoffice flexible endoscopy. Patients were managed by functional endoscopic sinus surgery for purpose ofexcisional or incisional biopsy.Results: The current study included 96 patients with a mean age of 49.09± 7.43 years and an age range of 39 to67 years. There were 42 males and 54 females. The results of complete evaluation have shown the followingpathologies at the end of the study: nasal polyposis (31, 32.3%), chronic rhinosinusitis without polyp (16,16.7%), antrochoanal polyp (14, 14.6%), inverted papilloma (11, 11.5%), frontoethmoidal mucocele (7,7.3%), concha bullosa (4, 4.2%), squamous cell carcinoma (3, 3.1%), rhinolith (2, 2.1%), fibrous dysplasia(2, 2.1%), adenocarcinoma (2, 2.1%), malignant melanoma (1, 1.0%), cavernous hemangioma (1, 1.0%),pyocele in concha bullosa (1, 1.0%) and non Hodgkin’s (1, 1.0%). Therefore, in the current study, nasalpolyposis was the commonest cause of unilateral sinonasal disease followed by chronic rhinosinusitiswithout polyp, antrochoanal polyp and inverted papilloma. The rate of malignant neoplasms was low.Conclusion: Differentiating the neoplastic nature form non-neoplastic nature of unilateral nasal pathologyis the most critical management step and in the current study, nasal polyposis was the commonest causeof unilateral sinonasal disease followed by chronic rhinosinusitis without polyp, antrochoanal polyp andinverted papilloma. The rate of neoplastic malignant conditions was low.